2000
DOI: 10.1017/s0012162200000335
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of universal screening for primary speech and language delay: findings from a systematic review of the literature

Abstract: This paper reports on a systematic review of the literature commissioned to examine the feasibility of universal screening for speech and language delay. The results, based on an examination of productivity figures, including positive predictive ability and likelihood ratio, indicate that a number of screening tests are adequate. Sensitivity was generally lower than specificity, and study quality was inversely related to both sensitivity and likelihood ratio, suggesting that it is easier to identify accurately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(42 citation statements)
references
References 63 publications
1
39
1
1
Order By: Relevance
“…Screening tests that attempt to identify a specific condition, for example LD, rather than general developmental delay, tend to have low sensitivity and specificity (Law et al 2000b). Up to 60% of cases of speech and language delay at 2 to 3 years of age may resolve spontaneously, but at the time of identification it is not possible to predict which children with language problems are likely to have persistent problems.…”
mentioning
confidence: 99%
“…Screening tests that attempt to identify a specific condition, for example LD, rather than general developmental delay, tend to have low sensitivity and specificity (Law et al 2000b). Up to 60% of cases of speech and language delay at 2 to 3 years of age may resolve spontaneously, but at the time of identification it is not possible to predict which children with language problems are likely to have persistent problems.…”
mentioning
confidence: 99%
“…Two systematic reviews of screening instruments for speech and language delay have been published (Law, Boyle, Harris, Harkness & Nye, 2000a;Nelson, Nygren, Walker & Panoscha, 2006), both reaching similar conclusions. The more recent of these, which formed the basis for a recommendation by the US Preventive Services Task Force (USPSTF), concluded that '…the evidence is insufficient to recommend for or against routine use of brief, formal screening instruments in primary care to detect speech and language delay in children up to 5 years of age' (USPSTF, 2006, 497).…”
Section: Commentarymentioning
confidence: 73%
“…7,8 The percentage of CD in this study was higher than that found in the general population (2.3 to 24.6%). 31 However, no prior studies of CD (including language disorders, speech disorders, and pragmatic skill disorders) have been conducted in similar populations in our country. In the literature, authors have mainly studied language disorders.…”
Section: Discussionmentioning
confidence: 97%